Analysis of Engineering Drawings and Raster Map Images - Henderson, Thomas C.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
This book covers up-to-date methods and algorithms for the automated analysis of engineering drawings and digital cartographic maps. The Non-Deterministic Agent System (NDAS) offers a parallel computational approach to such image analysis. The book describes techniques suitable for persistent and explicit knowledge representation for engineering drawings and digital maps. It also highlights more specific techniques, e.g., applying robot navigation and mapping methods to this problem. Also included are more detailed accounts of the use of unsupervised segmentation algorithms to map images. Finally, all these threads are woven together in two related systems: NDAS and AMAM (Automatic Map Analysis Module).
Introduction -- Segmentation and Vectorization -- Text and Graphics Analysis in Engineering Drawings -- A Structural Model for Engineering Drawings -- Non-Deterministic Analysis Systems (NDAS) -- Map Background and Form Separation -- Road and Road Intersection Extraction -- Other Semantic Feature Segmentation -- Rewrite Rules for Grammar G -- MNDAS User Manual -- Color Information from Legend of USGS Map.
Keywords: Engineering; Remote sensing; Computer vision; Engineering; Signal, Image and Speech Processing; Computer Imaging, Vision, Pattern Recognition and Graphics; Image Processing and Computer Vision; Remote Sensing/Photogrammetry.